Strategi Konten Audio Visual dalam Meningkatkan Branding: Studi Kasus Instagram @agromaritim.ipb - Adila, Fatimah Azzahra Citra; Saleh, Amiruddin (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
The development of digital technology has encouraged changes in improving institutional image, particularly through social media. Instagram has become an effective platform for institutional branding. This study aims to analyze the audiovisual content strategy used by the Instagram account @agromaritim.ipb and the challenges faced in strengthening its branding. This research employs a descriptive qualitative method through observation, active participation, interviews, and literature review. Primary data were obtained from internship activities at the Directorate of Agro-Maritime Community Development (DPMA IPB), while secondary data came from literature and official media. The findings show that the audiovisual content strategy is carried out through planning, production, and publication stages, following Regina Luttrell’s Circular Model of SOME (sharing, optimizing, managing, engaging), which helps enhance brand awareness and institutional image. The main challenges include limited human resources, editing equipment, and Instagram algorithm changes. Recommendations include improving team capacity, updating equipment, and conducting regular evaluations of content performance.
Keywords: Audiovisual Content; Branding; Communication Strategy; Instagram; The Circular Model of Some